A149 ENDOSCOPIC BALLOON DILATION IS A SAFE AND EFFECTIVE THERAPEUTIC INTERVENTION FOR PATIENTS WITH SMALL BOWEL CROHN'S DISEASE. (1st March 2018) - Reeson, M; Fedorak, R; Teshima, C W; Zepeda-Gomez, S; Halloran, B P
Abstract: Background: Crohn's disease (CD) is an inflammatory bowel disease that is characterized by chronic transmural inflammation of the gastrointestinal (GI) tract which can become complicated by the formation of strictures. CD can affect any part of the GI tract with 30–40% of patients having isolated small bowel CD. Complicated CD carries with it significant risk factors for the patient that can often only be alleviated through surgery or medication. However, the advent of Endoscopic Balloon Dilation (EBD) has allowed for temporary relief of obstructive symptoms and could potentially be an alternative therapy that prolongs the need for surgical intervention. Aims: This study is conducted to assess the safety and efficacy of EBD in patients with small bowel CD. Methods: A retrospective chart review was undertaken to examine all patients with small bowel CD who underwent BAE between July 2013 and August 2017. The data collection included patient demographics, disease characteristics, procedural characteristics, and stricture dilation data. Results: 152 BAEs (84 DBE, 68 SBE) were performed on 82 patients (45 female). The mean age at the time of the BAE was 53.4 ± 15.7 years. The mean disease duration was 17.4 ± 14.0 years. Fifty (61.0%) patients had undergone a previous gastrointestinal surgery. Of the 152 procedures, 84 (55.3%) required EBD, constituting 58.5% (48) of the total patients. In total, 191 strictures were dilated; 75.9% (145) were native strictures, 24.1% (46) were anastomotic strictures. There were a total of 3 (2.0%) complications, and there were no perforations or deaths. Thirty-five procedures (23.1%) involved a non-traversable stricture; in 25 (71.4%) of these procedures, the non-traversable stricture prevented the endoscopist from EBD. Conclusions: Endoscopic Balloon Dilation is a safe and effective intervention for the treatment of small bowel Crohn's disease and is likely under-utilized as an endoscopic tool. EBD can alleviate obstructive symptoms for both patients who have had previous resections or those with primary stenosis. In some patients, EBD may be effective enough to prolong or prevent the need for surgical resection. Funding Agencies: CEGIIR (The Center of Excellence for Gastrointestinal Inflammation and Immunity Research)